The Importance of Musical Improvisation in Primary School - Lejko, Maja (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter explores musical improvisation as a key form of creativity that stimulates children's imagination. Musical improvisation is defined as a learning skill that develops through practice, intellectual growth, and experience. It enables children to express their originality through music while enhancing rhythmic, harmonic, and melodic skills. Particular emphasis is placed on the importance of introducing improvisation at an early stage of education, as it activates cognitive processes. The chapter examines various types of improvisation, highlighting that vocal improvisation is used less frequently than instrumental and rhythmic improvisation. Effective improvisation involves making free yet purposeful musical choices within certain boundaries. The teacher's role is crucial in fostering students' intrinsic motivation, with the focus placed on the learning process rather than the final product. Despite its positive impact, improvisation remains underutilized in teaching practices. Children can achieve meaningful improvisation through simple patterns and diverse activities, contributing significantly to their overall musical development.